PENGARUH NILAI PELANGGAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi kasus pada penumpang KA Kaligung Mas di Stasiun Poncol Semarang) - Ikasari, Ajeng Utami; Suryoko, Sri; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
KA Kaligung Mas is a local train, route Semarang - Tegal Tegal â€“Semarang. departing from Semarang Poncol Station as first Station. In an effort to maintain relationships with customers, service quality is the key to retaining customers and providing high value through customer value. The problem in the center of competition in the transportasion industry is the decrease of the train passenger from 2010-2012, in 2011 decrease 36% and 2012 decrease 50% from the first year 2010. Customers will compare the quality of services provided by the facility what they are and what value they get from KA Kaligung Mas. This study aimed to determine the effect of Customer Value and Quality Service to Customer Satisfaction KA Kaligung Mas . The population in this study is the customers Kaligung Mas passenger trains.. The research sample was taken 100 first responders and sampling techniques accidental sampling is then conducted purposive sampling. Measurement scales using Likert scale. In the analysis of the data using simple linear regression and multiple regression test with the help of the program PASW 18.00. Testing the hypothesis the researchers used Customer Value and Quality Service has positive and significant impact on customer satisfaction, either partially or simultaneously. Views of Variable Quality of Service with the 5% significance obtained t value table is 1.6606, where the t value of (8.289)> t table (1.6606) so the hypothesis received the greatest impact on customer satisfaction in the amount of 41.2% and with a 5% significance obtained t value table is 1.6606, where the t value (5.933)> t table (1.6606) so the hypothesis is accepted. Variable influence on Customer Value Customer Satisfaction 26.4%. Simultaneously, variable Customer Value and Service Quality on Customer Satisfaction effect of 43.3%. This means better service quality and customer value is high, it may increase Customer Satisfaction. The suggestions for increase comfort, through improved facilities such as a lack of cold air, train departure time in order to improve over time, pay attention to the condition of facilities such as seating and cleanliness of the car, improving quality in serving the passengers to be more comfortable when it is in train and is expected to always maintain reputation of the company in order to increase customer confidence. Â